2018
DOI: 10.1007/s00264-017-3747-0
|View full text |Cite
|
Sign up to set email alerts
|

The antegrade angle-stable locking intramedullary nail for type-C distal femoral fractures: a thirty four case experience

Abstract: The IAIN and half-threaded cancellous screws provided a reliable fixation that facilitated uncomplicated outcomes and uneventful early mobilization in treating type-C fractures of the distal femur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…With nail osteosynthesis, the majority of recommendations regarding extra-articular distal femoral fractures, as well as periprosthetic femoral fractures with a firmly anchored prosthesis and open box design, are for permissive full weight-bearing [21,22,23,24]. This is also consistent with recent biomechanical analyses of this form of osteosynthesis, which show a high axial weightbearing capacity for retrograde femoral nails [6,35].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…With nail osteosynthesis, the majority of recommendations regarding extra-articular distal femoral fractures, as well as periprosthetic femoral fractures with a firmly anchored prosthesis and open box design, are for permissive full weight-bearing [21,22,23,24]. This is also consistent with recent biomechanical analyses of this form of osteosynthesis, which show a high axial weightbearing capacity for retrograde femoral nails [6,35].…”
Section: Discussionsupporting
confidence: 73%
“…A total of 23 papers were included in the analysis [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33], including four retrospective comparative studies comparing non-weight-bearing, partial weight-bearing, and full weightbearing [11,13,14,22]. With regard to isolated lateral plate osteosynthesis, permissive full weight-bearing according to ability was allowed in at least some patients in 6 out of 10 papers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports show that nailing for type C3 is associated with the worse range of motion outcomes among all distal femoral fracture patterns [ 1 ]. Management of type C3 with a new locking intramedullary nail is reported as a reliable fixation method [ 42 ]; however, it is not a standard of care and the nail is not accessible easily worldwide. An external fixator may also be used for stabilization, but it leads to delayed weight bearing and may lead to knee stiffness and further complications in distal femoral fracture management [ 5 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-introduced articles, there are several other exciting studies included in this issue. Zhao et al reported their initial experience of the newly designed antegrade interlocking angle-stable intramedullary nail combined with half-threaded cancellous screws in the treatment of type C (AO/OTA classification) distal femoral fractures [36]. Li et al verified that continuous vibration therapy and seven day intermittent vibration therapy pattern can achieve better improvement of fracture union [37].…”
Section: Yingze Zhangmentioning
confidence: 99%